Unleashing their potential: a critical realist scoping review of the influence of dogs on physical activity for dog-owners and non-owners - Rock Melanie J; Toohey Ann M (BMC, 2011)
Abstract Background Dog-owners tend to be more physically active than non-owners; however, dogs have also been shown to inhibit physical activity for non-owners, under some circumstances. Methods We conducted a scoping review to identify studies pertaining to the influence of dogs on physical activity for both dog-owners and non-owners, and adopted a critical realist orientation to draw inferences about the positive and negative impact of dogs via their affect on physical and social environments. Results We identified 35 studies from disparate literatures for review. These studies confirm that dog and owner behaviors affect shared physical and social environments in ways that may influence physical activity patterns, not only among dog-owners but also among non-owners. The direction of influence appears to be most positive in neighborhoods exhibiting high levels of social cohesion, socioeconomic status, perceived safety, dominant culture, or all of these. In disadvantaged neighborhoods, the health of women as well as older adults may be disproportionately affected by dog and owner behavior. Conclusions While dogs have the potential to increase physical activity for both dog-owners and non-owners, the presence or absence of dogs will not have a standard effect across the physical and social environments of all neighborhoods. Dogs' contributions to shared environments in ways that support physical activity for all must be leveraged. Thus, specific contextual factors must be considered in relation to dogs when planning neighborhood-level interventions designed to support physical activity. We suggest this population health topic merits further investigation.